2023
DOI: 10.1371/journal.pone.0277285
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of programmed death ligand-1 in tumor-associated macrophages affects chemotherapeutic response in ovarian cancer cells

Abstract: To better understand the mechanism of chemoresistance in ovarian cancer cells, we aimed to investigate the influence of macrophages on the tumor cell response to carboplatin and identify the genes associated with chemoresistance. We mimicked the tumor microenvironment (TME) using a co-culture technique and compared the proliferation of ovarian cells with and without macrophages. We also examined M1 and M2 marker expression and the expression of key TME genes. Post the co-culture, we treated ovarian cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, a meta-analysis of PD-L1 expression in OC revealed that PD-L1 does not have prognostic value in OC [ 339 ], in contrast to BC where a similar meta-analysis identified high PD-L1 expression as a negative prognostic factor [ 340 ]. However, PD-L1 upregulation has been associated with the development of carboplatin resistance in OC [ 341 ]. CD24, one of the OCSC markers, is expressed at higher levels than PD-L1 in OC, and interacts with Siglec-10 expressed on TAM, leading to anti-phagocytic activity of TAM and immune evasion.…”
Section: Cancer Immunogenicity and Evasion Of Immunosurveillance Of O...mentioning
confidence: 99%
“…However, a meta-analysis of PD-L1 expression in OC revealed that PD-L1 does not have prognostic value in OC [ 339 ], in contrast to BC where a similar meta-analysis identified high PD-L1 expression as a negative prognostic factor [ 340 ]. However, PD-L1 upregulation has been associated with the development of carboplatin resistance in OC [ 341 ]. CD24, one of the OCSC markers, is expressed at higher levels than PD-L1 in OC, and interacts with Siglec-10 expressed on TAM, leading to anti-phagocytic activity of TAM and immune evasion.…”
Section: Cancer Immunogenicity and Evasion Of Immunosurveillance Of O...mentioning
confidence: 99%